1998
DOI: 10.1126/science.282.5388.430
|View full text |Cite
|
Sign up to set email alerts
|

RNAi in C. elegans : Soaking in the Genome Sequence

Abstract: perhaps silencing tr&scriPtion at the &us. The alternative is that interference may prevent the processing or translation of the endogenous transcript. Several observations are most consistent with interference at a posttranscriptional step. First, only the sequences present in the mature transcript apDear to be effective at inducing interference. u e completion of the Caenorhabditis terference, two other remarkable features of Promoter and intron sequences appear to be elegans genome sequence represents a RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
309
0
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 591 publications
(328 citation statements)
references
References 7 publications
6
309
0
8
Order By: Relevance
“…Culture conditions, method of delivery and parasite stage Most studies have evaluated RNAi in parasitic nematodes using the soaking technique applied to C. elegans [14], with worms maintained in a simple medium containing the dsRNA at concentrations usually in the mg/ml range. Often, culture fluids are supplemented with liposome preparations (such as lipofectin) to increase the efficiency of RNA uptake into cells.…”
Section: Rna Interferencementioning
confidence: 99%
See 1 more Smart Citation
“…Culture conditions, method of delivery and parasite stage Most studies have evaluated RNAi in parasitic nematodes using the soaking technique applied to C. elegans [14], with worms maintained in a simple medium containing the dsRNA at concentrations usually in the mg/ml range. Often, culture fluids are supplemented with liposome preparations (such as lipofectin) to increase the efficiency of RNA uptake into cells.…”
Section: Rna Interferencementioning
confidence: 99%
“…For RNAi to be a truly effective tool in parasitic nematodes, it is desirable that the silencing RNA molecules are passed from one stage to the next and, therefore, mediate RNAi when gene transcription is 'switched on'. This is the case in C. elegans, in which an interference effect can persist for several days and could, in some cases, be inherited by subsequent generations [14]. However, it is not yet clear whether this mechanism is present in parasitic nematodes.…”
Section: Rna Interferencementioning
confidence: 99%
“…RNA interference (RNAi) is a recently described phenomenon whereby gene-specific double-stranded RNA (dsRNA) induces degradation of target mRNA with consequent sequence-specific inhibition of gene expression+ Originally reported in Caenorhabditis elegans , RNAi has been described in organisms as diverse as Trypanosoma brucei (Ngo et al+, 1998), Planaria (Sanchez Alvarado & Newmark, 1999), Hydra (Lohmann et al+, 1999), and Drosophila (Misquitta & Paterson, 1999)+ In plants, a variety of RNA-mediated silencing mechanisms are referred to as posttranscriptional gene silencing (PTGS) (Wassenegger & Pelissier, 1998), whereas PTGS in the fungus Neurospora has been termed "quelling" (Cogoni et al+, 1996)+ The mechanism of RNAi is at present poorly understood+ Given the gene-specific nature of RNAi, dsRNA needs to interact specifically with its target mRNA+ Whether there exist cellular factors that enhance dsRNA-mRNA recognition and how and in which compartment mRNA degradation is initiated are among the open questions+ Recently, several genes involved in the RNAi pathway have been identified in C. elegans, namely the rde (Tabara et al+, 1999) genes and mut-7 (Ketting et al+, 1999)+ rde-1 is part of a multigene family with homologs in plants, animals, and in fission yeast, but its precise function is not known+ The mut-7 gene bears the signature motif of RNase D and might represent one of the ribonucleases involved in mRNA degradation+ Interestingly, some rde as well as mut-7 mutant animals have enhanced levels of transposon mobilization, suggesting that in C. elegans one of the functions of RNAi might be to protect the organism from transposition damage by mobile elements+ In quellingdeficient Neurospora cells, the mutant gene qde-1 has similarity to RNA-dependent RNA polymerase of plants, suggesting that RNA synthesis by this enzyme might contribute to the PTGS response in this organism (Cogoni & Macino, 1999a)+ Furthermore, recently another gene qde-3, a member of the RecQ DNA helicase family, has been shown to be required for the activation and maintenance of gene silencing in Neurospora crassa (Cogoni & Macino, 1999b)+ To induce RNAi, dsRNA is delivered into cells using various methods depending on the organism's biology: the most common one being microinjection of synthetic dsRNA+ In C. elegans it is also possible to soak worms in dsRNA solutions (Tabara et al+, 1998), and by an unknown mechanism, the dsRNA makes its way into cells+ In trypanosomes we have shown that transient expression of tubulin dsRNA from plasmid constructs or electroporation of synthetic tubulin dsRNA causes degradation of tubulin mRNA (Ngo et al+, 1998)+ This resulted in a transient block of tubulin synthesis with the arrest of cytokinesis and consequent accumulation of cells with two nuclei, two kinetoplasts (mitochondrial genome), two basal bodies, and two flagella+ After tubulin synthesis resumed, trypanosomes progressed through the cell cycle one more time, duplicated basal bodies and flagella, and carried out nuclear and kinetoplast division+ At this point long slender trypanosomes became large almost spherical cells, which we na...…”
Section: Introductionmentioning
confidence: 99%
“…Until 1998, Fire and his colleagues validated that the phenomena of gene expression inhibition also by sense RNA was induced by contaminative double-stranded RNA generated during in vitro transcription [2]. This finding led to a series of RNAi-mediated gene silencing studies in many organisms such as worm [3,4], fly [5,6], mammalian [7][8][9] and plant [10] as well. Now RNAi has become a powerful tool to study gene function and explore the gene expression regulation mechanism, as well as provide a new approach for gene therapy.…”
Section: Introductionmentioning
confidence: 99%